Kontrol Kualitas Mikrobiologis Sarang Burung Walet (Collocalia Sp.) melalui Karantina Hewan Juanda, Surabaya - Oktorina, Retno; Indarjuliaanto, Soedarmanto; Soejartiningsih, Soejartiningsih; Isnaeni, Isnaeni; Wasito, Wasito (2004)
.